Effectiveness of Oral Rinsing Solutions on Mucus, Odor, and Plaque in the Hospitalized Elderly in Taiwan. (July 2019) - Chen, Su-Chih; Weng, Li-Chueh; Tsai, Shu-Chuan; Wang, Shu-Ming; Han, Hui-Mei
This quasi-experimental and pretest–posttest study was conducted in Taiwan. The effectiveness of three types of oral rinsing solutions (normal saline, 0.2% chlorhexidine [CHX], and boiled water) was compared among 120 elderly patients (40 patients per group). Data on oral mucus, odor, and plaque were collected at admission on Day 1 (Time [T] 0), Day 4 (T1), Day 7 (T2), and Day 10 (T3). The results showed that the oral health condition in terms of mucus, plaque, and odor improved significantly over time. The effect for the oral condition did not differ significantly among the three groups, except for oral odor. At T2, the CHX group experienced higher oral odor than did the boiled water group (Solutions × Time interaction, F = 3.967, p = .002). Boiled water appears to be a safe and effective oral rinsing solution for hospitalized elderly patients.